Aloe Vera Functionalized Magnetic Nanoparticles Entrapped Ca Alginate Beads as Novel Adsorbents for Cu(II) Removal from Aqueous Solutions - Surbhi Lilhare; Sunitha B. Mathew; Ajaya Kumar Singh; Sónia A. C. Carabineiro (Nanomaterials, 2022)
CABs (Ca alginate beads), AVCABs (Aloe vera Ca alginate beads), and AVMNCABs (Aloe-vera functionalized magnetic nanoparticles entrapped Ca alginate beads) were developed as adsorbents for the removal of Cu(II) from aqueous solutions. The materials were characterized using Fourier-transform infrared (FTIR) spectroscopy, high-resolution scanning electron microscopic (HR-SEM) analysis, X-ray diffraction (XRD), energy-dispersive X-ray (EDX) spectroscopy, and a vibrating-sample magnetometer (VSM). The effect of several parameters, such as pH, time, temperature, adsorbent dose, etc., were investigated. The adsorption isotherm of Cu(II) was adjusted best to the Langmuir model. The maximum adsorption capacities were 111.11 mg/g, 41.66 mg/g, and 15.38 mg/g for AVMNCABs, AVCABs, and CABs, respectively. The study of the adsorption kinetics for Cu(II) ions on beads followed a pseudo-second-order kinetic model, with a very good correlation in all cases. The adsorption studies used a spectrophotometric method, dealing with the reaction of Cu(II) with KSCN and variamine blue.